2017
DOI: 10.1177/1461444817738235
|View full text |Cite
|
Sign up to set email alerts
|

Libraries as redistributive technology: From capacity to culture in Queensland’s public library network

Abstract: Australia is currently rolling out one of the most expensive and ambitious infrastructure projects in the nation’s history. The National Broadband Network is promoted as a catalyst for far-reaching changes in Australia’s economy, governmental service provision, society and culture. However, it is evident that desired dividends, such as greater social engagement, enhanced cultural awareness and increased civic and political participation, do not flow automatically from mere technical connection to the network. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…In the current study, the district's population and library network showed an absolutely negative correlation in which the government must be vigorous and adhere to the public library manifesto to close the gap before it is too late (Table 3). The modern library uses digital technology and infrastructure to ensure easy access to resources and to support new modes of self-learning, self-expression, experimentation, and entertainment (Wyatt et al, 2018). Therefore, public information and digital literacy education should be regulated in such a way that the public can fully participate in literacy, use technology to search for resources, and participate in government affairs.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the district's population and library network showed an absolutely negative correlation in which the government must be vigorous and adhere to the public library manifesto to close the gap before it is too late (Table 3). The modern library uses digital technology and infrastructure to ensure easy access to resources and to support new modes of self-learning, self-expression, experimentation, and entertainment (Wyatt et al, 2018). Therefore, public information and digital literacy education should be regulated in such a way that the public can fully participate in literacy, use technology to search for resources, and participate in government affairs.…”
Section: Discussionmentioning
confidence: 99%
“…Also common are reflections on the changing institutional role of libraries resulting from digitalization (Joint, 2008, Ashcroft 2011, Goulding 2012, their growing importance as 'content aggregators, access managers, and educators in digital literacy' (Norman, 2012, 25), the role of libraries in government surveillance and big data generation (Vaidhyanathan & Bulock, 2014;Gangadharan 2016), and their evolution into social gathering places that provide access to the digital world (Black & Pepper, 2012;Nicholson & Petrović, 2018). Also worth noting is that public libraries are, for some, the only point of access to the Internet (Cohron, 2015) and to education about technology use (Kinney, 2010;Cranco, 2016;Wyatt, Mcquire & Butt, 2018). Finally, research on the unintended consequences of the growing reliance on volunteers in public libraries is important here as well (Casselden & Dawson, 2019) as such volunteers are typically less well equipped to support the digitalization effort.…”
Section: Public Libraries As Reserves Of Cultural and Digital Capitalmentioning
confidence: 99%
“…While some Wi-Fi-cafes exist and public hotspots are increasing, libraries continue to stand out in offering these services for free (Jaeger et al, 2012; Rimmer, 2014; Strover, 2019). Scholars have noted that libraries have been successfully evolving along with their communities and adapting their programming and services accordingly (Coward et al, 2018; Houghton et al, 2013; Montague, 2015; Perryman and Jeng, 2020; Rimmer, 2014; Strover, 2019; Willet, 2016; Wyatt et al, 2018). Rather than becoming obsolete or irrelevant, public libraries are increasingly offering digital access and information focussed programming (Strover, 2019; Willet, 2016).…”
Section: Introductionmentioning
confidence: 99%